Analysis of Rendering Technology on the development of the film and television Industry and Global Cultural Exchange - Ouyang, Weiyu (Transactions on Computer Science and Intelligent Systems Research, 2025)
This study examines the impact of rendering technology on the development of the film and television industry as well as global cultural exchange. With the rapid growth of computer graphics, advanced rendering technologies have become an essential part of visual narratives and cross-cultural communication. The study examines how ray tracing, High Dynamic Range (HDR) imaging, and neural rendering affect content dissemination, cultural presentation, and production efficiency. A mixed-methods approach includes technical analysis of rendering algorithms, industry case studies (e.g., Avatar, Mandalorian), and statistical evaluation of box office and streaming data from 2000 to 2022. The study results show that advances in rendering technology have dramatically improved production efficiency, a 68 per cent increase in virtual production efficiency, and market performance, a 27 per cent increase in global box office revenues. At the same time, experimental data showed a 15% increase in audience retention for HDR content, demonstrating the technology's contribution to cultural accessibility. However, the study also found problems with global rendering practices, such as algorithmic bias and resource inequality. These findings provide an essential reference for policymakers and industry leaders to promote the equitable development of technology and the production of culturally inclusive content.